Long-term efficacy and safety of endotherapy for management of biliary anastamotic strictures following liver transplantation. (13th March 2011) - Putta, S; Sagar, V; Gunson, B; Haydon, G; Freshwater, D; Holt, A; Pathmakanthan, S; Ferguson, J
Abstract : Introduction: Biliary anastomotic strictures are among the commonest biliary complications following liver transplantation. Endoscopic therapy including balloon dilatation of stricture and maximal stent placement, is widely used as the preferred means of managing these patients.1 2 However, endoscopic therapy is not standardized and there is very limited prospective data to support the long-term efficacy of this approach. The aim of our study is to assess the safety and long-term efficacy of endotherapy in the management of biliary anastamotic strictures complicating liver transplantation. Methods: This was a prospective observational study carried out at the liver transplantation unit, Queen Elizabeth Hospital, Birmingham, United Kingdom, between June 2000 and September 2010. In June 2000, the liver transplant unit in Birminghamintroduced a new protocol for managing biliary anastamotic strictures complicating orthotopic liver transplantation. The new protocol entailed a sequence of clearly defined clearly defined endoscopic interventions including balloon dilatations and stent insertions at regular intervals. A total of 1414 adult patients underwent liver transplantation. 81 (6%) patients were diagnosed with biliary anastomotic strictures during this period. Results: Endoscopic therapy was successful in 61% of patients referred with anastomotic strictures with a median intervention/stent free follow-up of 54 months. Patients required a median of 3 endoscopic procedures and two 24 F balloon dilatations to adequately treat the stricture. Three patients (3%) had recurrent stricture and two of these were successfully retreated with endotherapy. A total of 261 endoscopic procedures were undertaken and complications included mild to moderate pancreatitis (n = 9), Cholangitis (n = 4) and stent migration (n = 2). The rate of pancreatitis per endoscopic procedure was 3%. Severe pancreatitis or death were not reported. Twenty patients underwent biliary reconstruction. Conclusion: We report one of the very few prospective studies looking at the long-term efficacy and safety of endoscopic therapy in the management of anastamotic biliary strictures. Endoscopic balloon dilatation and stenting is a safe and efficacious means of treating biliary anastomotic strictures complicating liver transplantation.